The electrical conductive behaviours of polymer-based three-phase composites prepared by spatial confining forced network assembly - S. Kormakov; D. Wu; J. Sun; X. Gao; X. He; X. Zheng; I. Skopincev; N. Memetov; A. Tkachev; Z. Zhi (eXPRESS Polymer Letters)
Spatial Confining Forced Network Assembly (SCFNA) method is an effective method for the enhancement of electrical conductivity. In the current paper, a composite material consisting of polydimexilsiloxane (PDMS) and short carbon fiber (SCF) was modified by adding graphene nanoplateletes (Gr) at a concentration of 1~4 wt% into the composite system. The electrical properties of the obtained samples were compared with those prepared by compression molding to evaluate the effectiveness of SCFNA. The results showed that the addition of graphene increased the electrical conductivity of the composites by more than 4 orders of magnitude. Meanwhile, a polymer-based three-phase composite with the highest electrical conductivity of 287 S/m was obtained utilizing the SCFNA method in the present work.